Meetings, bloody meetings (London : Video Arts, 1976)
The video demonstrates how the techniques, disciplines and logic of running a meeting are parallel to those of conducting a court case. The lessons of the video will be valuable wherever meetings are held and participants imperfect.
Keywords: Meetings; Communication in management